2011
DOI: 10.1109/jstsp.2011.2165525
|View full text |Cite
|
Sign up to set email alerts
|

Joint Decoding of LDPC Codes and Finite-State Channels Via Linear-Programming

Abstract: This paper considers the joint-decoding problem for finite-state channels (FSCs) and low-density parity-check (LDPC) codes. In the first part, the linear-programming (LP) decoder for binary linear codes is extended to joint-decoding of binary-input FSCs. In particular, we provide a rigorous definition of LP joint-decoding pseudo-codewords (JD-PCWs) that enables evaluation of the pairwise error probability between codewords and JD-PCWs in AWGN. This leads naturally to a provable upper bound on decoder failure p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, this assumption may not hold for some cases. The LP decoding for finite-state channels is proposed in [13] and we can consider the symbol-pair read channel with finite state. To develop the LP decoding algorithm for such channel is a future work.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assumption may not hold for some cases. The LP decoding for finite-state channels is proposed in [13] and we can consider the symbol-pair read channel with finite state. To develop the LP decoding algorithm for such channel is a future work.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we consider the problem of low-complexity joint linear-programming (LP) decoding of low-density The dashed curves are computed using the union bound based on joint-decoding pseudo-codewords observed at 2.67 dB as described in [11] and the dash-dot curves are obtained using the state-based JIMPD described in [23]. The circle-solid curves are computed using Algorithm 1.…”
Section: Discussionmentioning
confidence: 99%
“…IV, the decoder performance results and conclude in Sec. V. Due to space limitations we omit many of the proofs, but they can be found in [20]. …”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the ESD channel matrix is column-orthogonal under OSTBC, satisfying . Thus, the ZF detection is simply (11) Note that the symbol is unquantized and thus can be further processed by soft-input soft-output decoder. Under Q-OSTBC, nonetheless, ZF detection does not admit such a simple form, due to the reason that the columns of channel matrix are not fully orthogonal.…”
Section: A Disjoint Zf Receivermentioning
confidence: 99%
“…For transmissions with higher-order modulations, the authors suggest transforming to an equivalent system with QPSK. On the other hand, Flanagan [10] proposed a unified framework for LP-based receivers, while Kim and Pfister considered the joint-decoding problem for finite-state channels [11]. Furthermore, without introducing a large number of extra variables, the authors in [12] extended the treatment of non-affine QAM mapping proposed in [10] for MIMO-OFDM systems.…”
mentioning
confidence: 99%